Development of web-based GIS for traffic management system with obstacle avoidance technique using open source software - Nik Yusoff, Nik Mohd Ramli (2014)
Distribution of road information on the internet is an enforcing factor for the authorities. This is due to the capability of the internet to disseminate information and provide georelated information analyses with no location restrictions. Web-based GIS has been used to distribute road information and provide shortest path analysis on the internet. However, the function of the analysis on the internet is still limited. The shortest path is a well-known network analysis that exists in traffic management systems. It provides the shortest route calculation between two points for road users. However, this function could not help to avoid its users from the congested areas due to the presence of obstacles on the roads. Therefore, the main objective of this study is to improve the traffic management system by implementing the shortest path analysis with obstacle avoidance technique. This is to avoid the presence of obstacles on the roads. In order to calculate the shortest path between two nodes, Dijkstra algorithm was utilized. Obstacle avoidance technique was implemented in this algorithm to avoid the congested areas. A web-based traffic management system was developed using open source software in this study. Verification of the shortest path calculation result obtained from the traffic management system was done via comparison of the performance and result with the use of Quantum GIS (QGIS) software and Waze application. Qualitative validation was run in order to test the function of obstacle avoidance technique in 50 km, 100 km, and more than 150 km route lengths with the presence of one, two, and three obstacles respectively. The system also was tested in urban, sub-urban, and rural areas to investigate the functionality of the system. For quantitative validation, the system was validated in terms of the time travel and fuel consumption. User satisfaction test was conducted concerning website acceptability and performance testing was made during this research. The shortest path result from the traffic management system produced similar result to QGIS. The obstacle avoidance technique has worked successfully in avoiding the presence of obstacles in different lengths of roads and different numbers of obstacles in a route. User satisfaction test results showed that most of the respondents agreed that this system could help the administrators in managing road activities effectively and provide the shortest path analysis with obstacle avoidance technique for road users in avoiding congested roads.